The role of institutional quality in the international trade of a Latin American country: Evidence from Colombian export performance - Carlos Abreo; Ricardo Bustillo Mesanza; Carlos Rodríguez González (Journal of Economic Structures, 2021)
This paper analyses the relevance of Colombian institutional quality in recent years in terms of the performance of its exports within a framework of trade openness. Based on the trade gravity model, we examine the effect of governance on the evolution of Colombian exports through an econometric approach that identifies, on the one hand, the influence of institutional quality, and on the other hand, the influence of the institutional distance between Colombia and its trading partners. We use a panel data set for 2005-2018, through which the export flows from Colombia to 136 of its trading partners are considered. The findings indicate that Colombian institutional quality and the institutional distance between the country and its partners are statistically significant and affect its foreign sales. Similarly, there is a prominent influence of regulatory quality and the rule of law variables in the performance of Colombian exports in relation to other variables included in the model. We conclude that the Colombian government must improve its institutional quality considerably as a fundamental step towards boosting its overseas sales, not least because the country's institutional distance from the world average is notable, which also affects its exports.
Keywords: 330; Exports; Free trade agreements; Institutional quality; Trade; Trade balance; Trade gravity model